Хроника обыкновенного следствия - Леке Алексис (Безнаказанность преступления, 2004)
Экземпляры: ф. 3 (20160725) / Инвентарный номер: 52216 / Цена: 10.00 / Авт.знак: Л 43 / ГРНТИ: 17.82 / ББК: 84(4Фра)